Determining the Effects of Cup Waterer on Growth Performance of Growing and Finishing Pigs - C. M. Vier; S. S. Dritz; M. D. Tokach; M. A. Gonçalves; F. Gomez; D. Hamilton; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2018)
Two studies were conducted to evaluate the growth performance of growing-finishing pigs in response to different ratios of cup waterers to pigs and different locations of the cup waterers within a pen under commercial conditions. In Exp. 1, 1,134 pigs (initial pen average BW of 35.7 ± 1.17 lb) were housed in pens that provided 6.85 ft2/pig and were used in a 113-d trial during summer months (May through September). Pens of pigs were blocked by location within the barn and allotted to treatments in a randomized complete block design. There were 14 replicate pens per treatment and 27 pigs per pen. Treatments consisted of 1, 2, or 3 cup waterers per pen, resulting in 27, 13.5, and 9 pigs per cup waterer, respectively. From d 0 to 45, increasing the number of cups per pen resulted in a quadratic increase (P<0.05) in the percentage of days that cups needed to be cleaned in order to remove fecal material. From d 80 to 113, with more waterers per pen, there was a linear increase in days the waterers were cleaned (P<0.05). For growth performance, there was no evidence of treatment effect from d 0 to 74 (P>0.10); however, from d 74 to 114 and overall, increasing the number of cup waterers per pen resulted in a linear increase in average daily gain (ADG) and final BW (P<0.05). Overall, there was no evidence of differences observed for average daily feed intake (ADFI) and feed efficiency (F/G) (P>0.10). In Exp. 2, 1,134 pigs (initial pen average BW of 34.7 ± 0.60 lb) were housed in pens that allowed 6.85 ft2of space per pig and were used in a 126-d trial during winter months (October through February). Pens of pigs were randomly allotted to 1 of 3 treatments in a randomized complete block design with location within the barn being the blocking factor. There were 14 replicates per treatment and 27 pigs per pen. Treatments consisted of a 1 cup waterer installed 42 in. from the feeder; 2 cup waterers installed 24 in. and 48 in. from one side of the feeder; and 2 cup waterers installed 24 in. from each side of the feeder. Overall, there was no evidence for differences among treatments regarding the percentage of waterers that needed to be cleaned (P>0.10). For growth performance, no significant treatment effects were observed from d 0 to 70 (P>0.10). From d 70 to 126 and overall, ADG was increased when pens were equipped with a 1 cup waterer located on each side of the feeder compared to pens with 2 cup waterers located on the same side of the feeder, with pens with 1 waterer intermediate (P<0.10). However, there was no evidence for an overall treatment effect on ADFI, F/G, and final BW (P>0.10). Results from this study indicate the optimal water cup to pig ratio changes as pigs increase in body weight. The linear improvement in growth performance as the number of drinking devices increased suggests water availability becomes more critical at heavier weight. Positioning of cup waterers within a pen is also an important factor to be taken into account, with a 1 cup waterer installed on either side of the feeder providing the highest growth rate. However, increasing the number of cups increased management associated with cleaning cups during summer months, but not during winter months. Further characterization of the interactions of cup waterer number, finishing pig weight, and cup waterer cleanliness on growth performance is needed.
Keywords: growth; drinker; water; growing-finishing pigs